The Representation of Women’s CEO Image in Online Media - Diah Kristina; Melsiana Shera Rita Ramadona (Lingua Cultura, 2019)
The research focused on the representation of women in the news about the absence of women in Uber’s CEO candidates from the perspective of feminist stylistics by Sara Mills. Five news texts from five different websites published during August 2017 were analyzed; they were Washington Post, Daily Mail, Inverse, Gizmodo, and Fortune. The method used was a qualitative research method with the approach of critical discourse analysis of Sara Mills. By applying three levels of analysis which was analysis at the level of the word, phrase/sentence, and discourse, this research aimed to analyze how women were represented linguistically in the online news of Uber’s CEO candidates and to discover the reason why women were represented in the way they were. The findings reveal that women remain underrepresented in news media. It is proved by the dominance of women as the object in the stories. Moreover, women are represented as ‘glass cliff position’, minority, and a way to recreate the good image in the company. The gender stereotypes, the background story of Uber, the male-dominated industries, and the prevalent condition become the reasons why women represented that way.